1981
DOI: 10.2134/agronj1981.00021962007300050018x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N Fertilization and Cutting Schedules on Stockpiled Tall Fescue. II. Forage Quality1

Abstract: Tall fescue (Festuca arundinacea Schreb.) is the coolseason grass used most frequently to extend the grazing season in mid‐latitude states of the midwestern and eastern United States. Insufficient information is available regarding the influence of fertilization and harvest management on the quality of stockpiled tall fescue forage available during winter. Results of two field experiments dealing with the influence of cutting and N fertilization management on stockpiled tall fescue quality and chemical composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
42
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 8 publications
9
42
1
Order By: Relevance
“…Research has shown stockpiling forage to be economically beneficial to the producer (18,20) while maintaining adequate yield (8,15) and nutrition levels for various classes of livestock (3,6,17). The cost of producing and storing forage for the winter months is often the largest expense incurred and is usually the most labor‐intensive practice used by graziers.…”
Section: Stockpiling Forage For Late Season Grazingmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown stockpiling forage to be economically beneficial to the producer (18,20) while maintaining adequate yield (8,15) and nutrition levels for various classes of livestock (3,6,17). The cost of producing and storing forage for the winter months is often the largest expense incurred and is usually the most labor‐intensive practice used by graziers.…”
Section: Stockpiling Forage For Late Season Grazingmentioning
confidence: 99%
“…Appropriate species selection can allow producers to claim the highest level of nutrients available and thus maximize livestock production. Among the species used for stockpiled forage, tall fescue has been found to be an excellent forage because of its ability to maintain yield and quality better than many other grasses throughout late autumn and early winter (2,3,13). In the spring following stockpiling, fescue continues to yield well (13).…”
Section: Stockpiling Forage For Late Season Grazingmentioning
confidence: 99%
“…2). Research from West Virginia has shownthat stockpiled tall fescue has a seasonal low in Mg concentration duringmid‐February (3). The lack of a treatment difference early in our study waslikely a result of Mg leaching from the leaves over winter and little grassgrowth.…”
Section: Magnesium Concentration Of Tall Fescue Foragementioning
confidence: 99%
“…Stockpiled fescue provides many producers with deferred winter grazing that can reduce the need for conserved forages or supplements (11). The initiation date and N management of fescue stockpiles are two areas that have received research attention (4,6,11). In a companion report to the current study, we found that splitting applications of 40 or 80 lb N/acre increased the probability of achieving designated yield goals of stockpiled tall fescue but results were affected by rainfall (12).…”
Section: Introductionmentioning
confidence: 99%